The effect of epoxidized natural rubber (ENR 50) as a compatibilizer on spear grass filled low density polyethylene/soya spent powder - S.T. Sam; Nurul Hani; H. Ismail (Universiti Kebangsaan Malaysia, 2015)
Composite based on spear grass with low density polyethylene (LDPE)/soya spent powder (SSP) were prepared by using twin screw extruder at 150oC. The spear grass (SG) loading was ranged from 0 to 15%. A compatibilizer, epoxidized natural rubber (ENR 50) with 50 mol % epoxidation was added. The effect of filler content and compatibilizer on the properties of LDPE/ SSP composite was studied. The results indicated that the increase of SG loading leads to the reduction of tensile strength and elongation at break (Eb), whereas the Young’s modulus has increased. Differential scanning calorimeter (DSC), indicated that the melting temperature and crystallinity of the composites decreased with the increase of SG loading. After the addition of ENR 50, the melting temperature increases from 98.33 to 98.63oC for 95% LDPE, 5% SSP and 5% SG, whereas the crystallinity of the same ratio decreased from 31.92 to 28.13%.